Experimental realization of mode-splitting resonance using microring resonator with a feedback coupled waveguide. (3rd August 2018) - Chen, Wenping; Xiao, Huifu; Liu, Zilong; Han, Xu; Liao, Miaomiao; Zhao, Ting; Tian, Yonghui
Abstract: We propose and experimentally demonstrate a mode-splitting device using a microring resonator (MRR) with a feedback coupled waveguide (FCW). For the proposed device, a pair of counter-propagating coupled modes exist in the MRR owing to the FCW, which is different from traditional ways of introducing roughness or center defects. We obtain the splitting of the transmission spectrum with a splitting wavelength of 0.37 nm and a notch depth of 21.87 dB. Moreover, the temporal coupled-mode theory is adopted to fit the experimental results and analyze the dependence of the transmission spectrum on the coupling coefficient κ. The experimental results are in good agreement with the simulations.